Difusi Inovasi Pemanfaatan Website Pasirkemilu.desa.id sebagai Promosi UMKM di Desa Pasir Kemilu Kecamatan Rengat Kabupaten Indragiri Hulu Provinsi Riau - Vivi Olivia Almariski; Tantri Puspita Yazid (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This research aims to see the diffusion of innovation in utilizing the pasirkemilu.desa.id website for promoting micro, small, and medium enterprises (MSMEs) in Pasir Kemilu Village. Currently in Indonesia, MSMEs are experiencing rapid development, so a strategy is needed to be able to compete and avoid bankruptcy. To change the behavior of MSMEs in Pasir Kemilu Village, the Pasir Kemilu Village Government has launched a program, namely the promotion of MSME products on the Pasir Kemilu Village website . The method used in this research is a qualitative method with data collection techniques carried out in 3 ways, namely interviews, observation and documentation and data analysis using miles and huberman models. Based on the results of the study it was found that the diffusion of innovation in utilizing the pasirkemilu.desa.id website for promoting micro, small, and medium enterprises (MSMEs) in Pasir Kemilu Village consists of four elements stated by Everett M. Rogers, namely Innovation, Communication channels, The time period, Members of a social system. The village website program as a promotion for MSMEs is highly beneficial for MSME practitioners, but in terms of its socialization aspect still needs improvement to make the program more widely known.